STUDI PERBANDINGAN ANALISIS STATIK EKUIVALEN DAN ANALISIS SPEKTRUM RESPONS DINAMIK PADA GEDUNG HOTEL DAN MALL 15 LANTAI DI MAGELANG: - - Yosafat Aji Pranata; Kaira Jesusa Prasodjo; Sutantra Hartono; Salal Hesy Bas Boys; Ricky Fransiskus Lumban Gaol; Faraz Haiatul Maknun1 (Politeknik Negeri Semarang, 2025)
The Aloon-Aloon Mall and Hotel Magelang is a fifteen-story building located in a seismically active zone due to the onvergence of the Eurasian and Indo-Australian Plates. This condition necessitates a structural design that complies with seismic resistance standards. However, no specific study has been conducted to evaluate the seismic response of this building based on local site conditions. Therefore, this research is essential to assess the structural performance under earthquake loads in order to enhance safety and reduce potential losses. Earthquake-resistant buildings are structures designed and constructed to minimize damage caused by seismic events. This study aims to evaluate the structural performance under seismic loading in accordance with SNI 1726:2019. The evaluation process was carried out through three-dimensional structural modeling using ETABS software. The seismic response of the 15-story mall and hotel building in Magelang City was analyzed using the equivalent static method and the response spectrum method. Structural modeling was performed using ETABS and SAP2000, with a focus on deformation and internal forces in beams and columns due to seismic loads. The analysis results obtained from both the equivalent static and response spectrum methods were compared. Based on the analysis results, the response spectrum analysis produced a larger deformation in the x-direction, amounting to 111.09 mm, compared to 105.10 mm obtained from the equivalent static analysis. Overall, the building is stable under the applied seismic loads, and no structural strengthening is required.